Honesty in Language in Public Figures’ Narratives in Tempo Magazine: A Forensic Linguistic Study - Musawir, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the level of linguistic honesty in public-figure narratives published in Tempo Magazine articles, employing the Statement Analysis in Linguistics (SAL) forensic-linguistic model developed by John Olsson. The investigation arises from concerns about public figures’ communication practices, which are often laden with manipulation when addressing legal cases—such as the “special fugitive” scandal. Using a qualitative-descriptive method, the study examines six narratives by public figures (including Anita Kolopaking, Yasonna Laoly, and Listyo Sigit Prabowo) based on three indicators: narrative structure, sequence of events, and association of the narrator with events. The analysis reveals varying levels of honesty: some narratives exhibit a coherent structure and high personal involvement, while others show signs of deception—such as excessive justification, inconsistent pronoun use, and convoluted narrative flow. These findings demonstrate that a forensic-linguistic approach is effective in identifying linguistic manipulation in public discourse and can serve as an evaluative instrument for assessing the integrity of public figures’ communication.